Narrating Literacy Practices at an Urban Secondary School in Surabaya - Susanto, Fajar; Rifai, Irfan (English Education Department, Faculty of Teacher Training and Education, Universitas PGRI Adi Buana Surabaya, 2017)
This study is aimed at narrating the implementation of literacy programme at an urban secondary school in Surabaya, focusing of how the school integrates and accommodates the concept of multilingualism (Java, Indonesian Language, English, French, and Japan) on its creative application and how the integration and accommodation of multilingual literacy is carried out on the day-to-day literacy practices. Drawing on qualitative data analysis gathered mainly through semi structured interviews with four teachers and two students and observations, the research findings suggest that school literacy programme is not only aimed at socializing and habituating the literacy culture within the school, but literacy programme facilitates spaces to accommodate the students’ creativity in the literacy practices through their participation, involvement and engagement in designing, managing and disseminating the school programme. It can be argued, therefore, that the literacy programme at the school transcends the expectations of the school in which the initial thought and expectation are only within the boundary of socializing and habituating the literacy culture within the school, but it transforms into more advance creative spaces for the students to learn languages and gain 21 century skills.